Synthesis of functional polymers: self-catalysed synthesis of functional polymers and nano-capsules and synthesis of degradable polymers using cyclic ketene hemiacetal ester monomers - Oh, Xin Yi (Nanyang Technological University, 2022)
Sustainability in chemistry has raised significant interest since 1980s. The objective of this doctoral thesis is to prepare sustainable functional polymers. In chapter 1, the general concept of radical polymerization was described. Also, several controlled radical polymerization (CRP) systems were discussed, including their principles and mechanisms. The concept of self-catalysis, polymerization-induced self-assembly (PISA), and degradable vinyl polymers were explained. The motivations and aims of each chapter were discussed. In chapter 2, self¬-catalyzed CRP using reversible complexation mediated polymerization (RCMP) was reported. Quaternary ammonium iodide (QAI)-containing monomers were synthesized and used in RCMP as a monomer and as well as a catalyst. The polymerization was performed without the addition of an extra catalyst. QAI-containing monomers were copolymerized with functional methacrylates and acrylates. In chapter 3, synthesis of nano-capsule was reported using self-catalyzed CRP and the nano-capsule was used as a heterogeneous RCMP catalyst. The nano-capsule was prepared using self-catalyzed polymerization-induced self-assembly (PISA). This vesicular nano-capsule possessing QAI functionality worked as a heterogeneous catalyst for the polymerization of several monomers. Also, good recyclability of this heterogeneous catalyst was demonstrated with ten cycles of methyl methacrylate (MMA) polymerization. The nano-capsule was further used as a nano-reactor to synthesize poly(methyl methacrylate) (PMMA) inside the cavity. In chapter 4, synthesis of degradable and chemically recyclable polymers was reported. 4,4-disubstituted five‐membered cyclic ketene hemiacetal ester (CKHE) (i.e., 4,4-dimethyl-2-methylene-1,3-dioxolan-5-one (DMDL) and 5-methyl-2-methylene-5-phenyl-1,3-dioxolan-4-one (PhDL)) monomers were synthesized and used for conventional radical polymerization. CKHE monomers were copolymerized with various co-monomers. Poly(4,4-dimethyl-2-methylene-1,3-dioxolan-5-one) (PDMDL) was degraded in hydroxide- and amine-assisted conditions. Degradations of hydrophilic and hydrophobic random copolymers of PDMDL were also studied. Chemical recycling was demonstrated with the recovery of DMDL monomer precursor from PDMDL degradation. In chapter 5, CRP of CKHE monomers (i.e., DMDL) was studied using reversible addition-fragmentation chain transfer (RAFT) polymerization and RCMP. Low-dispersity homopolymers, random copolymers, and a block copolymer of DMDL were prepared. A random copolymer of DMDL (i.e., PDMA-r-PDMDL, where PDMA is poly(N,N-dimethylacrylamide)) was degraded in a hydroxide-assisted condition. In this thesis, synthesis of functional polymers was demonstrated and their contribution to sustainability was presented. In Chapter 2 and 3, we used the catalytic monomers to catalyze polymerizations without additional catalyst. In Chapter 3, we prepared a heterogeneous catalyst with the catalytic monomer for recycle use in polymerizations. In Chapter 4 and 5, we synthesized degradable polymers and recovered the degradation product for monomer synthesis.